5(x-1)-6=-3

Simple and best practice solution for 5(x-1)-6=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-1)-6=-3 equation:


Simplifying
5(x + -1) + -6 = -3

Reorder the terms:
5(-1 + x) + -6 = -3
(-1 * 5 + x * 5) + -6 = -3
(-5 + 5x) + -6 = -3

Reorder the terms:
-5 + -6 + 5x = -3

Combine like terms: -5 + -6 = -11
-11 + 5x = -3

Solving
-11 + 5x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 5x = -3 + 11

Combine like terms: -11 + 11 = 0
0 + 5x = -3 + 11
5x = -3 + 11

Combine like terms: -3 + 11 = 8
5x = 8

Divide each side by '5'.
x = 1.6

Simplifying
x = 1.6

See similar equations:

| M=-3.2 | | 2+3*7-5+4=-35 | | 8x-3(5-2x)=11x | | .375-.25x=.5x-.75 | | 5+2(3k-7)=15 | | b-6b+14b=-18 | | 15xy^2+9x^2y=0 | | x=2x+-10 | | 8x+14+6x+36=180 | | -3(y+2)=21 | | x-32+5-6=13-16 | | 8.3z=4.1z+10 | | 2X^2-8X+8+1=0 | | 2x-.35=.45x+2.75 | | (-x)+1=0 | | 16x^3-62x^2-11x+12=0 | | (2x-10)+(3x+15)=180 | | 180-x=2(90-x)+32 | | 4x+3x+22=9(x+2)-6 | | (x-4)2+(y-5)2=25 | | 14=-d+5 | | 5+4x=-2x+65 | | 4.4=-5+x | | (2x-10)+(3x-15)=180 | | 6w-5w=14 | | 12b^2-75b+75=0 | | 1x+4y=208 | | 3r-10=r+4 | | (2x+10)+(3x+15)=180 | | 4y-6=2y+5 | | -10=h | | 3a+2a=-20 |

Equations solver categories